2012
DOI: 10.1007/s12519-012-0380-2
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term differences in right ventricular function in patients with congenital diaphragmatic hernia compared with controls

Abstract: Patients who underwent CDH repair continue to have differences in RV function years after repair. Follow-up is needed to determine how these differences impact cardiac function in adult survivors of CDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, RV strain was worse in patients with pulmonary hypertension than in those without pulmonary hypertension. The prognostic implications of this difference warrant further evaluation, but this is consistent with prior reports of decreased RV strain several years after CDH repair (32). These findings support the need for continued surveillance of ventricular function in these patients.…”
Section: Original Researchsupporting
confidence: 87%
“…However, RV strain was worse in patients with pulmonary hypertension than in those without pulmonary hypertension. The prognostic implications of this difference warrant further evaluation, but this is consistent with prior reports of decreased RV strain several years after CDH repair (32). These findings support the need for continued surveillance of ventricular function in these patients.…”
Section: Original Researchsupporting
confidence: 87%
“…Patients with CDH might present with anatomic and echocardiographic alterations of the left cardiac chambers (LV) ( 7 , 8 ), making the systemic circulation more dependent on the RV and exacerbating LV dysfunction ( 7 ). Additionally, the follow-up of children with CDH has demonstrated that altered RV function exists years after surgical correction ( 9 ). Given the importance of secondary cardiac function and pulmonary alterations in CDH, we performed an echocardiographic evaluation of the heart in a rabbit model of CDH ( 1 ) to verify whether myocardiac function exhibits primary or secondary alterations after birth and to correlate the data with histological findings.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria for HLHS patients included hospitalization, interventional cardiac catheterization, or cardiac surgery 2 months prior to the echocardiogram, or a history of a right ventriculotomy. Control patients were excluded if they had any cardiac abnormality except for a patent foramen ovale or if they had any other underlying medical issues such as reactive airway disease and diabetes . Control and HLHS patients were also excluded if they had poor echocardiographic image quality such that tissue Doppler imaging (TDI) and strain rate (SR) analysis could not be performed or if atrial or ventricular arrhythmias were present.…”
Section: Methodsmentioning
confidence: 99%